In Silico And In Vitro Characterisation Of Peptide Binding Sequence Of Trim25 Cc Domain Towards 14-3-3 Sigma Protein - Chiang, De Chen (2023)
14-3-3σ protein is the most diverged isoform among the seven isoforms of the 14-3-3 protein family. Unlike other 14-3-3 isoforms, its downregulation was demonstrated in various cancer and tumour development, which is in line with its function as an adaptor protein controlling cell cycle and development. TRIM25 is an E3 ubiquitin ligase that largely responsible for ubiquitin-mediated protein degradation. Interestingly, 14-3-3σ-TRIM25 interaction leads to 14-3-3σ ubiquitination and subsequent proteasomal degradation. Their exact interacting peptide sequence, however, has yet to be identified. The present study aimed to identify the peptide binding sequence of TRIM25 protein towards 14-3-3σ protein. A total of 5 peptides were identified from in silico bioinformatic analysis (motif search and multiple sequence alignment) for subsequent binding assay. The peptides were either purchased commercially, or synthesised in-house using Fmoc SPPS method, followed by purification using semi-preparative LC and mass-validated with LC-MS. 14-3-3σ protein was successfully expressed using E. coli expression system and purified with affinity chromatography. Interactions between the 6 peptides identified previously and the 14-3-3σ protein expressed were tested with 1H CPMG NMR assay, of which Peptide 1 with sequence 402KLPp(T)FG407 demonstrates the highest binding affinity to 14-3-3σ protein. Competitive CPMG NMR assay of Peptide 1 with Peptide 6 (a known 14-3-3σ binder) revealed substantial binding competition, suggesting that Peptide 1 shares similar binding site with Peptide 6 at the amphipathic pocket